Larval morphology of Chimarra argax Malicky 1989 (Trichoptera: Philopotamidae) with molecular data from Tan stream, Surat Thani province, southern Thailand - Tipkeaw, Chayanun; Tojo, Koji; Takenaka, Masaki; Rouangsuwan, Sarote; Laudee, Pongsak (Zootaxa, 2026)
The final-instar larva of Chimarra argax from southern Thailand is described and illustrated. The larva has a yellowish sclerotized head, pronotum, legs, and anal claws; the mesonotum, metanotum, and abdominal segments are membraneous. The anterior margin of the frontoclypeus in C. argax is slightly asymmetrical, featuring a central U-shaped incision flanked by two lump-like structures of unequal size, the left being slightly wider than the right. In addition, we analyzed the cytochrome c oxidase subunit I (COI) gene of the larva and confirmed adult material of C. argax, and compared the nucleotide sequences with those of closely related species. The resulting the COI Maximum Likelihood diagram supports the association of larval and adult C. argax as well as the assumption that C. argax is genetically distinct from C. shanorum, C. gether, and C. ariadne. Furthermore, C. argax and C. shanorum were assessed as being sister species forming a monophyletic clade.